Transforming blood supply chain management with Internet of things paradigm - Wijai Boonyanusith; Phongchai Jittamai (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
Internet of Things (IoT) paradigm has transformed the traditional healthcare system into the smart one. The IoT-based healthcare system is able to connect all available resources to operate healthcare services via the internet network. It would maximize the utilization of healthcare resources such as blood and blood products, which are scarce resources. Blood supply chain is a challenging system to manage, which researchers usually study for improved methodologies to boost its operation efficiency. Thus, this paper applied a content analysis in order to propose guidelines for enhancing and transforming the blood supply chain management based on the theoretical considerations in the IoT paradigm. The implementation strategies are provided to point out the issues that blood utilization and blood operational decision makings can be improved. Finally, the IoT-based framework of blood supply chain management is proposed to conceptualize the interactions between things, humans, processes, and service operations in the blood supply chain management.
urn:nbn:de:gbv:830-88217516; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; Blood supply chain; Internet of things; Healthcare services; Logistics management